Robust physiological mappings: from non-invasive to invasive - Syed, M.N.; Georgiev, P.G.; Pardalos, P.M. (Кибернетика и системный анализ, 2015)
The goal of this paper is to highlight the challenges on the three methods of data analysis, namely: robust, component, and dynamical analysis with respect to the epilepsey. A forward and inverse mapping model for the human brain is presented. Research directions for obtaining robust inverse mapping, and conducting dynamical analysis of the epileptic brain are discussed.